1999
DOI: 10.1016/s0014-5793(99)00681-x
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of suppressor of cytokine signaling (SOCS‐2) on growth hormone signal transduction

Abstract: A family of suppressors of cytokine signaling (SOCS) has recently been identified of which two members have been shown to block growth hormone (GH) signaling. Dose-response experiments were conducted in 293 cells and SOCS-1 and SOCS-3 were shown to inhibit the transcriptional activation of a GH-responsive element and suppressed Jak2 tyrosine kinase activity. SOCS-2 had two opposite effects: at low concentrations it inhibited GH-induced STAT5-dependent gene transcription, but restoration of GH signaling was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 23 publications
5
114
0
Order By: Relevance
“…However, it is likely that in transgenic mice overexpressing SOCS2, the observed increased growth is the result of a SOCS2 blockade of signaling by the more GH potent inhibitors, SOCS1 and SOCS3, at the GHR tyrosine motifs. (35,65,66) These observations indicate that SOCS1 and a lack of GH effect on metatarsal growth. (43,44,(54)(55)(56)68) However, Scheven and Hamilton did report GH stimulatory effects on metatarsal length, which is in contrast to the data of this current study.…”
Section: Discussionmentioning
confidence: 77%
“…However, it is likely that in transgenic mice overexpressing SOCS2, the observed increased growth is the result of a SOCS2 blockade of signaling by the more GH potent inhibitors, SOCS1 and SOCS3, at the GHR tyrosine motifs. (35,65,66) These observations indicate that SOCS1 and a lack of GH effect on metatarsal growth. (43,44,(54)(55)(56)68) However, Scheven and Hamilton did report GH stimulatory effects on metatarsal length, which is in contrast to the data of this current study.…”
Section: Discussionmentioning
confidence: 77%
“…Surprisingly, SOCS2 transgenic mice also show an increase in body weight, suggesting a dual role for SOCS2 in the GH signaling cascade. This is supported by in vitro experiments, in which only low-to-intermediate levels of SOCS2 show inhibitory action on GH signaling, whereas high levels of ectopic SOCS2 expression even increase STAT5 activation in response to GH stimulation (20,21). SOCS2 expression is induced by a number of different cytokines and hormones in many cell types (22).…”
Section: Endritic Cells (Dcs) Play Important Roles In Immune Recognmentioning
confidence: 85%
“…Until now, there is no conclusive evidence of any physiologic role of SOCS-1 and SOCS-3 in growth control (Greenhalgh & Alexander 2004). Although it was demonstrated that SOCS-2 binds to two phosphorylated tyrosines on the GHR, its mechanism of action (Greenhalgh et al 2005), its actions on GH signaling have been disputed, including positive and inhibitory effects on STAT activation in different models (Favre et al 1999, Greenhalgh et al 2002, 2005. We determined SOCS-1, -2 and -3 in Ames dwarf mice in order to establish the impact of undetectable GH levels on these proteins.…”
Section: Discussionmentioning
confidence: 99%